Optimization of Nursing Care for Patients Suffering from Mental Disorders in the Elderly and Senile Age - Idillaevna, Gaybullaeva Feruza; Furkatovna, Payzullayeva Vazira; Mamurjonovna, Khalilova Nilufar (European Journal of Life Safety and Stability (2660-9630), 2024)
Optimization of nursing care for patients with mental disorders in the elderly and senile age requires special attention and approaches. It is important to take into account the individual needs of each patient, as well as their physical and emotional state. Qualified nurses should develop and implement specialized care programs aimed at improving the mental health and general well-being of patients. The use of complex methods such as therapeutic communication, active listening and group activities can significantly improve the quality of care provided. The synergy between the medical and social aspects of care will create a more comfortable environment for older people suffering from various mental illnesses, contributing to their social integration and improving their quality of life. Professional interaction with relatives is also essential for the effective treatment and support of such patients. In addition, a key aspect of optimizing care is the training of nurses in specific methods of working with patients with mental disorders. This may include trainings on the value of emotional intelligence, creating a trusting atmosphere, and conflict management. Such skills are necessary for an adequate assessment of the patient’s condition and the provision of timely care. It is also important to introduce a multi-level approach to psychosocial support that takes into account various aspects of the lives of older people. For example, hobby activities, physical activity and psychotherapy can significantly improve the general condition of patients, contributing to psychological recovery and strengthening social ties. The system of regular monitoring of patients’ condition will allow nurses to effectively respond to changes in psychological health, as well as adapt existing care programs. The joint efforts of nurses, doctors and social workers will contribute to the creation of an optimal range of services and ensure an integrated approach to treatment.